Cerebellar Continuous Theta Burst Stimulation Facilitates Auditory–Vocal Integration in Spinocerebellar Ataxia. (8th July 2021) - Lin, Qing; Chang, Yichen; Liu, Peng; Jones, Jeffery A; Chen, Xi; Peng, Danhua; Chen, Mingyuan; Wu, Chao; Liu, Hanjun
Abstract: Clinical studies have shown the efficacy of transcranial magnetic stimulation in treating movement disorders in patients with spinocerebellar ataxia (SCA). However, whether similar effects occur for their speech motor disorders remains largely unknown. The present event-related potential study investigated whether and how abnormalities in auditory–vocal integration associated with SCA can be modulated by neuronavigated continuous theta burst stimulation (c-TBS) over the right cerebellum. After receiving active or sham cerebellar c-TBS, 19 patients with SCA were instructed to produce sustained vowels while hearing their voice unexpectedly pitch-shifted by ±200 cents. Behaviorally, active cerebellar c-TBS led to smaller magnitudes of vocal compensations for pitch perturbations than sham stimulation. Parallel modulatory effects were also observed at the cortical level, as reflected by increased P1 and P2 responses but decreased N1 responses elicited by active cerebellar c-TBS. Moreover, smaller magnitudes of vocal compensations were predicted by larger amplitudes of cortical P1 and P2 responses. These findings provide the first neurobehavioral evidence that c-TBS over the right cerebellum produces modulatory effects on abnormal auditory–motor integration for vocal pitch regulation in patients with SCA, offering a starting point for the treatment of speech motor disorders associated with SCA with cerebellar c-TBS.